2023
DOI: 10.3390/molecules28020853
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-Composition Analysis of Glass Chemical Composition Based on Time-Series and Clustering Methods

Abstract: The weathering of ancient glass relics has long been a concerned. Therefore, a systematic and more comprehensive mathematical model with which to correctly judge the category of ancient glass products whose chemical composition changes due to weathering should be established. This paper systematically analyzes and studies the changes in the composition of ancient glass products as a result of weathering of. We first analyze the surface weathering of glass relics and its correlation with three properties and es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“… Zou (2023) used time series and clustering methods for molecular compositional analysis of glass chemical compositions. Ye et al (2015) investigated new gray prediction models to predict four typical interval gray number sequences separately.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Zou (2023) used time series and clustering methods for molecular compositional analysis of glass chemical compositions. Ye et al (2015) investigated new gray prediction models to predict four typical interval gray number sequences separately.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, accurately predicting the chemical composition of glass before weathering is a prerequisite for achieving precise classification. Moreover, although several studies on the classification of glass types have been reported, for example, Zou et al [16] used one-way analysis of variance to subclassify glass artifacts. Li et al [17] employed a multivariate linear regression model for classifying unknown glass products.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this research is to analyze the statistical patterns and intrinsic relationships between the chemical compositions found in these two kinds of glasses, as well as to investigate and build prediction models between glass types and chemical compositions and to map their functional figures. In terms of research approach, this study employs a number of mathematical models for problem solving and model selection for each model's training effect before using the chosen model for prediction, analysis, and solution to improve the mathematical model's accuracy [2][3][4][5][6][7][8]. This is also the major focus of this article, which uses a portable X-ray fluorescence spectrometer to examine the chemical composition of ancient glass artifacts.…”
Section: Introductionmentioning
confidence: 99%